Old People and Their Needs as a Challenge for Education and Labor Market - Wieczorkowska, Magdalena (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
Ageing policy seems to be the priority for many states – including Poland – facing the ageing trends. Providing with support and inclusion of seniors into mainstream social life is the main strategy of actions on the international, regional, national and local level. The aim of the article is to show the relation between old people and educational and labor market as they are bi‑directional and very complex. Those areas are – next to health care – crucial in terms of active ageing and inclusive senior strategies. The article is based on desk research and the main method was analysis of existing documents. The main thesis of the paper states that: 1) there is an incongruity between real needs of old people and their satisfaction, 2) satisfying of the needs of the elderly meets barriers that are an effect of lack of qualified staff that could effectively meet those demands. First part of the paper presents ageing policy as a strategy on different levels of social policy. The second part presents educational and labor markets as two crucial areas of active ageing – old people are on one hand active participants on both of them and – on the other hand – they are beneficiaries of solutions and services provided by professionals in ageing. The aim of those analyses is to depict mutual relations and to provide recommendations on improvements in both of those areas.